Effect of Novel Rhythmic Physical Activities on Fundamental Movement Skills in 3- to 5-Year-Old Children. (28th December 2020) - Hu, Xin; Jiang, Gui-ping; Ji, Zhong-qiu; Pang, Bo; Liu, John
Abstract : Based on traditional rhythmic physical activities (TRPA), we created novel rhythmic physical activities (NRPA). The purpose of this study was to verify the effectiveness of NRPA in improving children's fundamental movement skills (FMS). 289 children (135 boys, 154 girls) from 3 to 5 years old were randomly divided into an experimental group and a control group. Tools of Test of Gross Motor Development-2, Tekscan instrument, and balance beam were to assess children's FMS. Two-way repeated measures ANOVA was used to analyze and compare the changes in the related parameters of locomotor, manipulative, and balance movement skills before and after intervention (groups × time ). NRPA performed significantly better than TRPA from pre- to posttest for FMS. Furthermore, NRPA had significantly higher posttest scores than TRPA. Therefore, NRPA could effectively promote the development of children's FMS due to the concept of the sensitive period of motor development, the variability of movement parameters, and the incomplete repeatability of practice methods.